Identifikasi Ragam Jenis Jamur di Taman Buah Lokal Mekar Lestari - Candra Pratama; Amalia Rezeki; Ferry F. Hoesain (Universitas Islam Negeri Mataram, 2023)
Mekar Lestari Local Fruit Park is a park managed by the Indonesian Center for Biodiversity Studies and Conservation. This park has a collection of local fruit plants located in Anjir Muara, Barito Kuala Regency. One of the potential organisms found in this area is fungi. The purpose of this study was to identify the types of fungi in the local fruit garden area